Auxiliary Structures-Assisted Radiotherapy Improvement for Advanced Left Breast Cancer - Lei, Runhong; Zhang, Xile; Li, Jinna; Sun, Haitao; Yang, Ruijie (Frontiers in Oncology, 2021)
Background: To improve the quality of plan for the radiation treatment of advanced left breast cancer by introducing the auxiliary structures (ASs) which are used to spare the regions with no intact delineated structures adjacent to the target volume. Methods: CT data from 20 patients with left-sided advanced breast cancer were selected. An AS designated as A1 was created to spare the regions of the aorta, pulmonary artery, superior vena cava, and contralateral tissue of the upper chest and neck, and another, designated as A2, was created in the regions of the cardia and fundus of the stomach, left liver lobe, and splenic flexure of the colon. IMRT and VMAT plans were created for cases with and without the use of the AS dose constraints in plan optimization. Dosimetric parameters of the target and organs at risk (OARs) were compared between the separated groups. Results: With the use of AS dose constraints, both the IMRT and VMAT plans were clinically acceptable and deliverable, even showing a slight improvement in dose distribution of both the target and OARs compared with the AS-unused plans. The ASs significantly realized the dose sparing for the regions and brought a better conformity index (p < 0.05) and homogeneity index (p < 0.05) in VMAT plans. In addition, the volume receiving at least 20 Gy (V20) for the heart (p < 0.05), V40 for the left lung (p < 0.05), and V40 for the axillary-lateral thoracic vessel juncture region (p < 0.05) were all lower in VMAT plans. Conclusion: The use of the defined AS dose constraints in plan optimization was effective in sparing the indicated regions, improving the target dose distribution, and sparing OARs for advanced left breast cancer radiotherapy, especially those that utilize VMAT plans.